Co-Occurrence of ANCA-Associated Vasculitis and Sjögren’s Syndrome in a Patient With Acromegaly: A Case Report and Retrospective Single-Center Review of Acromegaly Patients - Fuchs, Philipp S.; Lötscher, Jonas; Berkemeier, Caroline M.; Hirsiger, Julia R.; Ghosh, Adhideb; Li, Quan-Zhen; Deigendesch, Nikolaus; Christ, Emanuel; Navarini, Alexander A.; Recher, Mike; Daikeler, Thomas; Heijnen, Ingmar A. F. M.; et al. (Frontiers in Immunology, 2020)
Background: ANCA-associated vasculitis (AAV) and Sjogren’s syndrome (SS) are uncommon autoimmune diseases. The co-occurrence in the same patient has been rarely described. Acromegaly has been associated with autoimmune thyroiditis, but the prevalence of other autoimmune disorders such as AAV and SS has not been evaluated in acromegaly. Methods: Characterization of a patient with acromegaly and two rare autoimmune diseases - SS and AAV (microscopic polyangiitis (MPA)) - by autoantibody-array and whole exome sequencing (WES). A single-center retrospective review of acromegaly patient medical records to explore the prevalence of diagnosed autoimmune diseases. Results: We report a 50-year old Caucasian woman with a serologically (anti-SSA/Ro, anti-MPO-ANCA antibodies) and histologically confirmed diagnosis of symptomatic SS and MPA. SS with MPO-ANCA positivity preceded MPA. An exploratory autoantigen array detected a broad spectrum of autoantibodies. WES revealed heterozygous carrier status of the PTPN22 mutation R620W, which is associated with an increased risk for autoimmunity. A similar combination of positive anti-SSA/Ro autoantibodies and ANCA was only present in 5/1184 (0.42%) other patients tested for both antibodies in our clinic over six years. Amongst 85 acromegaly patients seen at our clinic in a twenty years period 12% had a clinically relevant immunological disease. Conclusion: We present a rare case of SS and AAV in a patient with acromegaly and multiple autoantibody specificities. Patients with SS and ANCA should be closely monitored for the development of (subclinical) AAV. Whether acromegaly represents a risk for autoimmunity should be further investigated in prospective acromegaly cohorts.